EVALUASI PERSYARATAN SUBSTANTIF, TEKNIS, DAN ADMINISTRATIF POLA PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (Studi Kasus pada Sebelas Puskesmas di Kabupaten Ngawi) - Cahyadi, Gery Fajar (Jurnal Ilmiah Mahasiswa FEB, 2017)
The study aims to evaluate the readiness of the Regional Work Unit (Satuan Kerja Perangkat Daerah/SKPD) to meet the substantive, technical, and administrative requirements of financial management of Regional Public Service Agency (Badan Layanan Umum Daerah). This descriptive qualitative research applies a case-study approach toward eleven public health centers (Puskesmas) proposing for PPK-BLUD in Ngawi regency, consisting of the Puskesmas in the district of Jogorogo, Kauman, Kendal, Tambakboyo, Paron, Sine, Walikukun, Pangkur, Bringin, Karanganyar, dan Kasreman. The eleven centers have completed the substantive, technical, and administrative requirements. The evaluation result on the substantive requirements shows that all institutions have owned a legal basis for its operation as public health centers, its implementation of PPK-BLUD, and its administration of public agencies providing goods/public services. In addition, the evaluation result on the technical requirements illustrates that the service performance in terms of their duties and functions are worth-managing for future achievement of the financial performance, as shown in the financial dependence and income growth. Meanwhile, the evaluation result on the administrative requirements reveal that all health centers proposing for PPK-BLUD have earned the full status of BLUD with values ranging between 90.20 up to 94.00.Key Word: Evaluation, Requirements, Public Service Agency, Community Health Center.